Kajian Identifikasi Penurunan Tren Curah Hujan, CDD dan CWD di Kota Kupang, Nusa Tenggara Timur - Wendel Jan Pattipeilohy; Destan Saktrianus Beis; Agus Sabana Hadi (Stasiun Pemantau Atmosfer Global Lore Lindu Bariri - Palu, 2022)
Changes in rainfall can cause a shift in the beginning of the dry season and the rainy season which can have an impact on various sectors, especially agriculture. Therefore, it is necessary to study climate change in the Kupang region, East Nusa Tenggara (NTT) through time series analysis of rainfall which can be identified by trend analysis and Probability Density function (PDF). This study aims to identify the trend pattern of the rain fraction, rainy days (HH), Consecutive Dry Days (CDD) Consecutive Wet Days (CWD) and the distribution of rainfall data in the 1991–2020 (30 years) period in the city of Kupang. The rainfall data used is observational rainfall data at the Kupang Climatology Station. Analysis of annual rainfall trends and rainy days showed an increase in the incidence of rainfall in the low category (0–20 mm)/day. While in the category of rain > 20mm / day it decreased, this caused the trend of the 20mm, 50mm and 100mm rain fractions in Kupang to be negative. The phenomenon of ENSO (El Niño and La Nia) affects the pattern of CDD and CWD in the city of Kupang, CDD and CWD trend analysis shows a downward trend of 0.4496 days / year and 0.054 days / year. PDF of the rainfall during the DJF period in Kupang city shows a significant change in the last 20 years and the chance of 5 rainy days in Kupang city is very high.